Factors affecting perception of working environment among manufacturing workers in Malaysia / Nur Hashimahtul Maziah Mohamed - Mohamed, Nur Hashimahtul Maziah (Faculty of Business and Management, 2019)
Every organization in this world are competing with each other to strive for success. A higher achievement of the organization are depending on its manpower or the human capital because employees are one of the main factors that contribute to the success of the organizations. On top of that, employee’s productivity is an important elements that indicate how well they are able to perform towards achieving the organization’s goals and objectives. These productivity among the employees are influence by various factors that need to be assessed so that it can be maintained to ensure their performance are consistence. Therefore, the aim of this research study is to investigate the factors affecting perception of working environment among manufacturing workers in Malaysia as employee’s level of productivity is indirectly affected when they perceived positive working environment. The objective that researcher tried to achieve are to determine the relationship between three different variables namely work-life balance, social dialogue and happiness with the perception of the working environment. Thus, this research will cover employees who work in manufacturing organizations located at Muar, Johor and Seremban, Negeri Sembilan. They are given a set of questionnaires that using 4-points Likert Scale through online methods and the data will be analysed using Statistics Package for Social Science (SPSS). The findings and results shows that social dialogue and happiness influenced the perception of working environment. However, the variable of work-life balance is said has no relationship with the dependant variable. Therefore, the results will provide the insights for employers in managing the workplace to influence employees’ perceptions as well as enhance the level of productivity.